The Effect of Profitability and Corporate Tax on Manufacturing Companies in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange for the 2014 – 2018 Period - Olivia (Outline Journal of Economic Studies, 2022)
This study aims to determine the influence of Profitability and Corporate Tax toward Capital Structure in food and beverage manufacturing companies listed at Indonesia Stock Exchange. The unit analysis and observation in this study is food and beverage manufacturing companies listed at Indonesia Stock Exchange, with total population of 18 companies. From this population, 10 companies are chosen by purposive sampling technique throughout 5 periods of time, specifically from 2014-2018 which sum up to 50 samples.The results of the research analysis show Profitability has a significant effect on and Capital Structure and Corporate Tax partially does not have significant effect on Capital Structure. The results showed that Profitability and Corporate Tax simultaneously have a significant effect on Capital STructure in food and beverage manufacturing companies listed at Indonesia Stock Exchange period 2014 – 2018. The results of this study are supported by the value of R square which means Profitability and Corporate Tax have an effect on Capital Structure. While the remaining is effected by other factors originating from outside this research model such as sales stability, activa structure, operational leverage, growth rate, control, characteristic of management, characteristic of creditors, rating agency, financial market condition, and financial flexibility.